Correlation of Liver Stiffness and Histological Features in Healthy Persons and in Patients With Occult Hepatitis B, Chronic Active Hepatitis B, or Hepatitis B Cirrhosis - Fung, James; Lai, Ching-Lung; Chan, See-Ching; But, David; Seto, Wai-Kay; Cheng, Charles; Wong, Danny Ka-Ho; Lo, Chung-Mau; Fan, Sheung-Tat; Yuen, Man-Fung (The American journal of gastroenterology, 2010)
Liver stiffness measurement using transient elastography has become a popular tool to assess liver fibrosis. The aim of this study was to determine liver stiffness values and histological features in healthy subjects and in patients with chronic hepatitis B (CHB). A total of 157 people were included (28 healthy subjects and 18 patients with occult hepatitis B infection, 102 with active CHB, and 9 with end-stage hepatitis B cirrhosis). Histology and liver stiffness measurements were obtained from all patients. The median liver stiffness in healthy subjects and in occult hepatitis B, active hepatitis B, and end-stage cirrhosis patients was 4.6, 4.2, 8.7, and 33.8 kPa, respectively. In healthy subjects and in patients with occult hepatitis B infection, none had significant fibrosis on histology, and all had liver stiffness <7.2 kPa. In patients with active CHB, 32 (31%) had liver stiffness >11.0 kPa, but only four (12%) had cirrhosis on histology. Using liver stiffness to predict cirrhosis in this group had a sensitivity of 100%, a specificity of 69%, a positive predictive value of 10%, and a negative predictive value of 100%. All nine patients with end-stage liver cirrhosis had liver stiffness >11.0 kPa. The overall area under the ROC curve (AUROC) for diagnosing cirrhosis using a cutoff of 11.3 kPa was 0.89. Liver stiffness measurement has an overall good diagnostic accuracy with excellent negative predictive value. However, in active CHB with elevated alanine aminotransferase (ALT) levels, the positive predictive value for diagnosing cirrhosis is poor, and further studies are needed to optimize the use of transient elastography in this important group.